Pemberdayaan Komunitas Perempuan Melalui Pelatihan Kerajinan Batik Berbasis Zero Waste dan Digital Marketing di Kota Solo - Darmaningrum, Kurniawati; Widyaswati, Rahmatya; Harsono, Mugi; Aryani, Novita; Cyntia, Ade Ilham; Isach, Sativa; Jati, Audita Karisma; As Sidiq, Isa Ali Ghufron (Jurnal Pengabdian UNDIKMA, 2024)
This community service activity aims to improve the skills of female heads of families in processing batik scrap waste into creative products with economic value, as well as increasing their entrepreneurial capacity through guidance in production, digital marketing, and financial management. This community service method used a training and mentoring approach. The partner of this activity was the Unity Fashion community, a women's community that focuses on developing skills in the fashion sector. The evaluation instrument for this activity used a questionnaire that measures the understanding, skills, and satisfaction of participants after participating in the training. The evaluation data were then analyzed descriptively. The results of this community service showed a significant increase in the skills and knowledge of partners, especially in terms of batik waste management and digital marketing, which had a direct impact on improving their family's economy. By empowering the female heads of families, it is hope that they will be able to become independent entrepreneurs who contribute to family welfare and environmental preservation through batik waste processing.